A secure communication scheme based generalized function projective synchronization of a new 5D hyperchaotic system. (27th March 2015) - Wu, Xiangjun; Fu, Zhengye; Kurths, Jürgen
Abstract: In this paper, a new five-dimensional hyperchaotic system is proposed based on the Lü hyperchaotic system. Some of its basic dynamical properties, such as equilibria, Lyapunov exponents, bifurcations and various attractors are investigated. Furthermore, a new secure communication scheme based on generalized function projective synchronization (GFPS) of this hyperchaotic system with an uncertain parameter is presented. The communication scheme is composed of the modulation, the chaotic receiver, the chaotic transmitter and the demodulation. The modulation mechanism is to modulate the message signal into the system parameter. Then the chaotic signals are sent to the receiver via a public channel. In the receiver end, by designing the controllers and the parameter update rule, GFPS between the transmitter and receiver systems is achieved and the unknown parameter is estimated simultaneously. The message signal can be finally recovered by the identified parameter and the corresponding demodulation method. There is no any limitation on the message size. Numerical simulations are performed to show the validity and feasibility of the presented secure communication scheme.